PERAN PEMBELAJARAN BERDIFERENSIASI DALAM MENGAKOMODASI KEBERAGAMAN SISWA BERKEBUTUHAN KHUSUS PADA KURIKULUM MERDEKA: STUDI LITERATUR DENGAN REFLEKSI PRAKTIK ADAPTASI PEMBELAJARAN DI SLB NEGERI 1 GOWA - Zainab, Addiva; Agung Nurmansyah, Bayu; Wulandani, M. Pd, Nur; Sulasminah, M. Pd, Dra. Dwiyatmi; Susanto Degu Duu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to conduct an in-depth analysis of the role of differentiated instruction in addressing the diversity of students with special needs within the Merdeka Curriculum, with a focus on its implementation at State Special School 1 Gowa. The background of this study stems from the gap between the concept of differentiated instruction and its implementation in practice, particularly in the field of special education. A qualitative approach was employed, combining a literature review with reflections on teaching practices. Data were collected from relevant scholarly sources as well as observations of instructional planning and implementation. The findings indicate that differentiated instruction has not yet been fully integrated into the planning phase, as evidenced by the use of instructional materials that are not fully tailored to individual student needs. Consequently, differentiation is more frequently applied during implementation through direct adaptation by teachers. Nevertheless, teachers demonstrated adequate adaptability, particularly in adjusting instruction for visually impaired students through multisensory strategies. Thus, this study concludes that the success of differentiated instruction depends not only on conceptual understanding but also on the alignment between planning, implementation, and support from the overall education system.